424. Southern Arizona Town: Homes Colonized by Kissing Bugs. Is Chagas Disease Being Transmitted?. (26th November 2018) - Beatty, Norman; Bradley-Behrens, Nicole; Love, Maria; Smith, Shannon; Ahmad, Nafees; Klotz, Stephen
Abstract: Background: Bisbee, Arizona is a small mining community established 1880, located 11 miles from the United States–Mexico border with a total population of 5, 500 residents. Homes in this town are revealing evidence of colonization by kissing bugs (triatomines), specifically Triatoma recurva, T. rubida, and T. protracta, which are known to harbor the causative agent of Chagas disease, Trypanosoma cruzi . Methods: Community members who were bitten by triatomines, provided specimens from their homes, and completed a home evaluation as well as point-of-care testing for Chagas disease (Chagas Detect™ Plus (CDP) Rapid Test, InBiosInternational, Inc.). Results: Twenty-two individuals from 17 households consented to participate and provided 117 triatomines collected from inside and/or outside their homes ( N = 70 T. rubida ; N = 36 T. recurva ; N = 11 T. protracta ). Trypanosoma cruzi DNA was detected by RT-PCR in 25.6% (30/117) of the total triatomines (31.4% (22/70) T. rubida ; 18.2% (2/11) T. protracta ; 16.6% (6/36) T. recurva ). The median age of homes was 91 years. Mean persons per home was 2.2; with 1.0 dog and 0.8 cat per home. Seventy percent of homes used either a swamp cooler or central air conditioning. Only one home had used pesticides in an attempt to exterminate insects. All homeowners reported various wildlife near their home, including javelina, pack rat, rock squirrel, mule deer, and raccoon (Figure 1). Homeowners were asked to correctly identify these triatomines in a photo line-up of similar insects, and 75% of participants made a successful identification of at least one triatomine, 90.9% being able to identify T. recurva . When asked whether they had changed their sleeping patterns due to triatomine bites, 45.5% (10/22) had done so. The same surveyed group rated their frustration with triatomines in their home on scale of 1–10 (10 being the most frustrated) revealing a mean rating of 6.6; with nine individuals rating 10. CDP rapid testing of these participants ( N = 22) were all-negative for serological evidence of T. cruzi infection. Conclusion: Despite exposure to T. cruzi -positive triatomines among these household residents, some having sustained hundreds of bites throughout the years, we do not have evidence of transmission of Chagas disease. These are preliminary findings and further study is underway. Disclosures: All authors: No reported disclosures.